Total power deficit estimation for isolated power system network using H∞ norm method - Jamri, Mohd Saifuzam; Kamarudin, Muhammad Nizam; Mohd Jamil, Mohd Luqman; Zakaria, Muhammad Iqbal (Institute of Advanced Engineering and Science, 2023)
An isolated electrical network with an independent local distributed generator is very sensitive towards the contingencies between load demand and supply. Although the network system has less complexity in term of structure, its stability condition is crucial due to its stand-alone operating condition. Hence, to monitor the stability of the network, total power deficit is the only variable that can be estimated. This study proposed to utilize the